A Comparison of Midazolam, Lorazepam, and Diazepam for the Treatment of Status Epilepticus in Children: A Network Meta-analysis. (August 2016) - Zhao, Zi-yu; Wang, Hong-ying; Wen, Bin; Yang, Zhi-bo; Feng, Kang; Fan, Jing-chun
Midazolam, lorazepam, and diazepam were recommended as emergent initial therapy for status epilepticus. However, there are no current studies to confirm the best agent for pediatric status epilepticus. We compared the efficacy of midazolam, lorazepam, and diazepam in treating pediatric status epilepticus using a network meta-analysis method. In total, 16 randomized controlled trials containing 1821 patients were included. Nonintravenous midazolam, intravenous lorazepam, and intravenous diazepam were more successful in achieving seizure cessation when compared with nonintravenous diazepam (odds ratio = 2.23, 95% credibility interval: 1.62, 3.10; odds ratio = 2.71, 95% credibility interval: 1.25, 5.89; odds ratio = 2.65, 95% credibility interval: 1.12, 6.29; respectively). Among lorazepam, midazolam, and diazepam, midazolam had the highest probability (surface under the cumulative ranking area [SUCRA] = 0.792) of achieving seizure cessation, and lorazepam had the largest probability (surface under the cumulative ranking area = 0.4346) of being the best treatment in reduction of respiratory depression. In conclusion, nonintravenous midazolam and intravenous lorazepam were superior to intravenous or nonintravenous diazepam, and intravenous lorazepam was at least as effective as nonintravenous midazolam in treating pediatric status epilepticus.